Parenting and child development : across ethnicity and culture - Khaleque, Abdul (California : Praeger, 2021)
"This research-based book covers the core components of modern parenting and child development across multi-ethnic and cross-cultural contexts in Asia, Africa, Europe, and North and South America, with a focus on the United States"--
Includes bibliographical references and index.
Keywords: Parenting; Child development